The Transformation of Kampung Arab Al-Munawarah Becomes a Tourism Object - Anisa, Nur; Heldayani, Eni (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The objective of this research is to identify the impact of transformation of Kampung Arab Al-Munawar Palembang into a tourism object. The writer uses the qualitative and descriptive method in this research. The data collected through survey method is by interviewing samples selected randomly to observe the effects of transformation and development experienced by development of Kampung Al-Munawar both socio-cultural and economic aspect of the community. The results of this research shows that the transformation of Kampung Al-Munawar has a positive effect on physical form of dwelling, economic, and social cultural aspects of the community. The forms of residental houses are going to be more beautiful and well maintained. The economy seems to be more always, with the appearance of several new ventures of community. Community became more consistent to maintain the customs and habits of Kampung Al-Munawarin in order not to be contaminated with the habits of visitors. Culture of the community is growing and preserved so that it can be known by the domesticpublic and overseas.